Why we came to the city - Jansma, Kristopher (Viking, 2016)
A "novel about a tight-knit group of twentysomethings in New York whose lives are forever altered by an unexpected tragedy... Five years after their college graduation, the devoted friends once known as "the Murphys" remain as inseparable as ever... As this...novel opens in December 2008, they are making their way through heavy snowfall to gather at a lavish art world holiday party. But for all the glitz and glamor, the festivities mark a more momentous evening than any of them realize... When a devastating blow threatens to tear them irreparably apart, they must struggle to carry on together."--